A geração de renda na política de assistência social: a intersetorialidade e territorialização no contexto do CRAS e da economia solidária - Souza, Adalvambete Alves de (2024)
The strategies of intersectorality and territorialization signal the contribution of a practice aimed at valuing the skills and culture of members of a given locality. With this in mind, public policies can develop actions taking into account the territory and the singularities existing in the population, in order to promote quality of life, through the generation of work and income. In view of this, the present work had the general objective of analyzing how social assistance incorporates intersectorality in its policy and can use this strategy as a means to develop actions with the solidarity economy thinking about the development of the territory. To this end, a qualitative approach was used, the objectives were descriptive and the procedures adopted were bibliographic, documentary and field research. Data collection was carried out on the Institutions' websites. Furthermore, a structured interview guide was used with two coordinators of the Social Assistance Reference Center (CRAS) in the city of João Pessoa. In the treatment and interpretation of research data, content analysis was carried out, according to the technique of Bardin (2016). With regard to work and income generation actions, the findings indicate that the Municipal Social Assistance Policy of João Pessoa has directed services with a professionalizing focus, aiming at preparation to meet the demands of the labor market, with a vision of individualizing the situation of vulnerability, without taking into account the integration of knowledge, territorial vocations and awareness and organization of individuals in a collective way. The results also demonstrate that there is a lack of work developed in an articulated manner between the sectors, presenting a lack of dialogue and strategy to meet common demands between both policies.